Hubungan Pengetahuan Gizi Orang Tua dan Pendapatan Orang Tua dengan Kepatuhan Orang Tua Dalam Penerapan Diet Autis pada Anak autis di SLB Autis Laboratorium UM Universitas Negeri Malang - Handayani, Poncowuri; Dewi, Mazarina; Kurniawan, Agung (citeus, 2019)
Autism is a behavioral deviation syndrome in children that involves sensory systems, communication skills, and socialization skills in community. Parental obedience in applying the diet should be consistent in order to reduce symptoms are undergone by children with autism. This study aims to determine the relationship between parental nutrition knowledge and parental income to parent’s obedience of complience in the application of autism diet in children with autism in the SLB Autis Laboratorium Malang State University. The type of this research is quantitative research with cross sectional study design. Parental knowledge was measured from a knowledge questionnaire, and income was measured by the per-capita income category per month and parental compliance was measured from Food Frequency Questionare (FFQ). The results showed that there was a significant correlation between parent’s nutritional knowledge and parent’s obedience to the application of the autism diet at SLB Autis Laboratorium Malang State University (p = 0,004) and there was a significant correlation between parent’s income with parent’s obedience to the application of the autism diet at SLB Autis Laboratorium Malang State University (p = 0,020). Suggestions for the next research to conduct more detailed research about per capita income of family by considering another factor.